Effect of granule properties on rough mouth feel and palatability of orally disintegrating tablets - Kimura, Shin-ichiro; Uchida, Shinya; Kanada, Ken; Namiki, Noriyuki (International journal of pharmaceutics, 2015)
[Display omitted] In this study, we evaluated the palatability of orally disintegrating tablets (ODTs) containing core granules with different particle sizes, coating, and types of materials using visual analog scales (VAS). Tableting the core granules into ODTs reduced rough mouth feel and improved overall palatability compared to the ingestion of core granules alone. Moreover, the evaluation performed immediately after spitting out ODTs demonstrated differences in rough mouth feel between ODTs containing placebo and core granules. Rough mouth feel was found to be significantly more intense with core granules with particle sizes ≥200μm. Since ODTs may contain taste-masked particles, palatability of ODTs containing coated core granules was also evaluated. Although coating with polymers impairs palatability, it was improved by coating the outer layer with d-mannitol. The effects on palatability of materials constituting core granules were also evaluated, with reduced rough mouth feel observed with core granules composed of water-soluble additives. Based on these data, receiver operating characteristic analysis was performed to determine the threshold VAS scores at which the subjects felt roughness and discomfort. In addition, the threshold particle size of the core granule contained within the ODT required for feeling roughness was determined to be 244μm. This study elucidated the effect of the properties of masking particles on the rough mouth feel and palatability of ODTs.